2017
DOI: 10.1111/icad.12218
|View full text |Cite
|
Sign up to set email alerts
|

Modelling habitat persistence and impacts of management on the habitats of an endangered butterfly

Abstract: In dynamic landscapes, effective species conservation requires an understanding of the spatial and temporal dynamics of species’ habitats. In this study, vegetation data across differently aged sites, site management history data and expert elicitation are used to estimate (i) expected habitat patch lifetimes and (ii) the impacts of habitat management history on how habitat quality changes through time for an early‐successional habitat specialist, the endangered false heath fritillary butterfly (Melitaea diami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…, Enright et al. , Fabritius and McBride ). Many species exhibit variability in their post‐disturbance time window of occurrence (Donner et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…, Enright et al. , Fabritius and McBride ). Many species exhibit variability in their post‐disturbance time window of occurrence (Donner et al.…”
Section: Discussionmentioning
confidence: 98%
“…). Therefore, modeling variation in the time window of occurrence for fire‐dependent species may allow the identification of important habitat areas, in addition to refining the appropriate time since fire at which to burn to regenerate habitat in any given area (Fabritius and McBride ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because false heath fritillary habitats are seldom occupied by other endangered species of regional interest, they are not the focus of habitat-focused conservation programs. The expected lifetime of an unprotected false heath fritillary habitat has been estimated to be 13.1 years, the quality of the habitat site starting to decrease 2-3 years after site maintenance because of the successional dynamics of the habitats (Fabritius and McBride 2017) and habitats requiring maintenance, e.g., mowing or grazing, at least every 5 years (Intke 2003).…”
Section: Case Study: False Heath Fritillary Conservation In Finlandmentioning
confidence: 99%
“…Based on existing knowledge of habitat succession at false heath fritillary meadows (Intke 2003, Fabritius andMcBride 2017), the tempo of habitat dynamics at false heath fritillary habitats was, however, often faster than this. Consequently, reports of habitat network surveys indicated that large proportions of habitats had already been destroyed in the process of habitat succession by the times of the surveys (Kekkonen and Rönkä 2009).…”
Section: Monitoring Of and Responding To Changes In The Habitat Networkmentioning
confidence: 99%